Differential predictors of DSM-5 PTSD and ICD-11 complex PTSD among African American women. Issue 1 (1st January 2017) - Powers, Abigail; Fani, Negar; Carter, Sierra; Cross, Dorthie; Cloitre, Marylene; Bradley, Bekh
ABSTRACT: Background : Complex posttraumatic stress disorder (CPTSD) is proposed for inclusion in the ICD-11 as a diagnosis distinct from posttraumatic stress disorder (PTSD), reflecting deficits in affective, self-concept, and relational domains. There remains significant controversy over whether CPTSD provides useful diagnostic information beyond PTSD and other comorbid conditions, such as depression or substance use disorders. Objective : The present study examined differences in psychiatric presentation for three groups: traumatized controls, DSM-5 PTSD subjects, and ICD-11 CPTSD subjects. Method : The sample included 190 African American women recruited from an urban public hospital where rates of trauma exposure are high. PTSD was measured using Clinician Administered PTSD Scale for DSM-5 and CPTSD was measured using clinician administered ICD-Trauma Interview. Psychiatric diagnoses and emotion dysregulation were also assessed. In a subset of women ( n = 60), emotion recognition was measured using the Penn Emotion Recognition Task. Results : There were significant differences across groups on current and lifetime major depression ( p < .001) and current and lifetime alcohol and substance dependence ( p < .05), with CPTSD showing the highest rates of comorbidities. CPTSD women also showed significantly higher levels of childhood abuse and lower rates of adult secure attachment. Multivariate analysis of variance showed significantly more severe PTSD and depression symptoms and, as expected, more severe emotion dysregulation and dissociation, compared to DSM-5 PTSD and traumatized control groups. Individuals with CPTSD also had higher levels of emotion recognition to faces on a computer-based behavioural assessment, which may be related to heightened vigilance toward emotional cues from others. CPTSD women had better facial emotion recognition on a computer-based assessment, which may suggest heightened vigilance toward emotional cues. Conclusions : Our results suggest clear, clinically-relevant differences between PTSD and CPTSD, and highlight the need for further research on this topic with other traumatized populations, particularly studies that combine clinical and neurobiological data.